Lactose crystallisation in concentrated whey: the influence of vat type. (26th September 2017) - Simeão, Moisés; DA Silva, Cleuber R; Stephani, Rodrigo; de Oliveira, Luiz Fernando C; Schuck, Pierre; de Carvalho, Antônio F; Perrone, Ítalo T
Abstract : This work aimed to describe the rate of lactose crystallisation in concentrated whey carried out using two different crystallisers, utilising central or lateral stirring. The lactose crystallisation rate differed between treatments, showing high values with use of the central stirrer. Under the experimental conditions, after 4 h of crystallisation, in neither of the vats was 70% lactose crystallisation achieved. With the standardised conditions applied in this study, with soluble solids, time, and stirring and rate cooling being constant, it was possible to verify the influence of the vat type on the rate of lactose crystallisation.